2012
DOI: 10.1038/jcbfm.2012.30
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Acute/Severe Hypoglycemia-Induced Neuron Death by Lactate Administration

Abstract: Hypoglycemia-induced cerebral neuropathy can occur in patients with diabetes who attempt tight control of blood glucose and may lead to cognitive dysfunction. Accumulating evidence from animal models suggests that hypoglycemia-induced neuronal death is not a simple result of glucose deprivation, but is instead the end result of a multifactorial process. In particular, the excessive activation of poly (ADP-ribose) polymerase-1 (PARP-1) consumes cytosolic nicotinamide adenine dinucleotide (NAD + ), resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 50 publications
2
30
0
1
Order By: Relevance
“…11,16,17,33 We also tested the protective effect of pyruvate and lactate, which can also be used by brain as alternative substrates to glucose through its metabolism by the tricarboxylic acid cycle. In agreement with previous studies, [37][38][39] we observed a reduction of neuronal death in the in vitro model by both substrates, while the effect of pyruvate was similar to that of D-BHB, lactate was less effective.…”
Section: Discussionsupporting
confidence: 93%
“…11,16,17,33 We also tested the protective effect of pyruvate and lactate, which can also be used by brain as alternative substrates to glucose through its metabolism by the tricarboxylic acid cycle. In agreement with previous studies, [37][38][39] we observed a reduction of neuronal death in the in vitro model by both substrates, while the effect of pyruvate was similar to that of D-BHB, lactate was less effective.…”
Section: Discussionsupporting
confidence: 93%
“…Experimental evidence indicates that changes in the concentration of three of the discriminant metabolites we identified—namely lactate, creatine, and taurine—can be associated with an increased oxidative stress [Jang & Kim, ; Lobysheva et al, ; Ribeiro, Silva, Rodrigues, Naia, & Rego, ; Won et al, ]. By being described that these molecules can have a protective effect by decreasing the formation of reactive oxygen species or the production of superoxide anion, their decrease in our patients can support the presence of an oxidative stress condition in autistic individuals.…”
Section: Discussionmentioning
confidence: 57%
“…The authors concluded that neuronal tissue appears to be able to handle excess lactic acid [48]. Several studies show that lactate may be the preferred energy substrate of activated neurons and is neuroprotective [49-54] and lactate may be a major substrate for the mitochondrial tricarboxylic acid cycle. Lactate preserves neuronal function in experimental models of excitotoxicity, posthypoxic recovery, cerebral ischemia, and energy deprivation and can sustain neuronal integrity as an alternative energy substrate.…”
Section: Exogenous Carbon Monoxide May Change Neurometabolism and Resmentioning
confidence: 99%
“…The authors concluded that increased brain lactate during hypoxia may be neuroprotective in IUGR piglets [55]. In a rat model of acute/severe hypoglycemia, Won and colleagues concluded that supplementation of glucose with lactate reduced neuronal death in the hippocampus and hypothesized that increasing brain lactate in this model offsets the decrease in NAD + due to overactivation of PARP-1 by acting as an alternative energy substrate that can effectively bypass glycolysis and be fed directly to the citric acid cycle to maintain cellular ATP levels [56]. Our results in newborn piglets preconditioned with inhaled CO before CPB/DHCA are also consistent with a change to lactate as the metabolic substrate and resulting neuroprotection [45].…”
Section: Exogenous Carbon Monoxide May Change Neurometabolism and Resmentioning
confidence: 99%